Plant exploitation and subsistence patterns of the Mesolithic in arid China: New evidence of plant macro-remains from the Pigeon Mountain site - Zheng, Xuefang; Peng, Fei; Wang, Shuzhi; Guo, Jialong; Wang, Huiming; Gao, Xing; Zhao, Zhijun (Frontiers in Earth Science, 2023)
The nature of the Mesolithic in China has not been studied much due to the few well-context sites discovered and excavated during this period. The situation also restricts understanding of human subsistence in the Mesolithic period in China, especially in the arid region. The present paper reports the flotation results at Locality 10 of the Pigeon Mountain site in northwest China. Ten species of plants in 6 families were identified, dominated by Agriophyllum squarrosum and Artemisia sieversiana. No firm evidence proves the domestication. Combined with the lithic artefacts in QG10, ancient people could utilise plant resources by constructing or expanding the food spectrum. It is the first systematic archaeobotany work in the Paleolithic site of Northwest China. The result reminds us that the enhanced utilization of wild plant resources is a vital subsistence for Mesolithic people in arid regions.